3³-2c²+3c-4-(c³-3c²-5)
для начала упростим выражение:
3³-2c²+3c-4-(c³-3c²-5)
раскрываем скобки
27-2с²+3с-4-с³+3с²+5=
изменяем порядок действий
-с³+(3с²-2с²)+3с+(27-4+5)=-с³+с²+3с+28
если c=2, то -с³+с²+3с+28=-2³+2²+3·2+28=-8+4+6+28=30
4x²-(2x³+4x²-5)
для начала упростим выражение:
раскрываем скобки
4x²-(2x³+4x²-5)=4х²-2х³-4х²+5=
изменяем порядок действий
-2х³+(4х²-4х²)+5=-2х³+5
если x=-3, то -2х³+5=-2·(-3)³+5=-2·(-27)+5=54+5=59
2p-(1-p²-p³)-(2p+p²-p³)
для начала упростим выражение:
раскрываем скобки
2p-(1-p²-p³)-(2p+p²-p³)=2р-1+р²+р³-2р-р²+р³=
изменяем порядок действий
(р³+р³)+(р²-р²)+(2р-2р)-1=2р³-1
если
, то![2\cdot(\frac{2}{3})^{3}-1=2\cdot\frac{8}{27}-1=\frac{16}{27}-1=\frac{16-27}{27}=\frac{11}{27} 2\cdot(\frac{2}{3})^{3}-1=2\cdot\frac{8}{27}-1=\frac{16}{27}-1=\frac{16-27}{27}=\frac{11}{27}](https://tex.z-dn.net/?f=2%5Ccdot%28%5Cfrac%7B2%7D%7B3%7D%29%5E%7B3%7D-1%3D2%5Ccdot%5Cfrac%7B8%7D%7B27%7D-1%3D%5Cfrac%7B16%7D%7B27%7D-1%3D%5Cfrac%7B16-27%7D%7B27%7D%3D%5Cfrac%7B11%7D%7B27%7D+)